WHEN A NOVEL AND A FILM MEET IN VIRTUAL CLASSROOM - Giyatmi (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2021)
The research aims at describing the teaching of screenification (ekranisasi) online. The writer uses Google Classroom integrated with Google Slides to create a Bitmoji, virtual classroom with a slide of presentation. There are pictures with links that can be clicked so that the students can find the materials in the slide. The using of Bitmoji classroom is applied to the 5th semester students of English Department. The writer uses questionnaire by Google Form to collect the data. To teach screenification (ekranisasi), the writer uses two chapters of Laura Ingalls Wilder’s On the Bank of The Plum Creek, namely Town Party and Country Party. For the film, the writer uses the video of Little House on the Prairie mini-series entitled Town Party Country Party. The two chapters and the video are inserted in the Bitmoji virtual classroom via links. The writer gives an assignment to find the process of screenification (ekranisasi). The students feel happy with the use of Bitmoji virtual classroom. They mention that the use of the novel and the video helps then to find the intrinsic elements of both versions so that they can find the process of screenification easily.